(untitled) (Comillas Journal of International Relations, 2021)
For more than 500 years, Iberoamerican countries have developed their own identity based on a common language, culture and history. The highest expression of this identity is the Ibero-American Summits, which began in 1991 following Spain’s proposal. These meetings have the ultimate aim of being a forum for cooperation and dialogue. Due to the changes that take place in the international arena, the Ibero-American Summits have been going through different crises caused mainly by the appearance of other regional integration forums, the lack of citizen participation, and the hegemonic role of Spain. To solve the crises, member opted for institutionalization (creation of SECIB and SEGIB) and the drafting of expert reports. Time has shown that these solutions are not effective enough to make the summits useful in today’s international scenario. Therefore, new reforms that change the raison d’être of the meetings must be carried out to ensure their survival.